An international football match experienced from within a 'working quarantine' – a photographic journey. Issue 2 (15th March 2021) - Halldorsson, Vidar
Abstract : The Covid pandemic has affected contemporary lives to unprecedented levels, including the world of sports, which have faced training and competition bans, matches and tournaments having been postponed or cancelled. However, the Union of the European Football Associations (UEFA) was keen to continue playing despite the pandemic and staged matches played behind closed doors. Thus, UEFA provided the involved parties with a strict protocol of how to organise and conduct matches in order to protect players and staff from contracting the virus, as well as to limit the risk of spreading the virus. This study provides a visual auto-ethnographical account of a European qualifier match between the women´s national teams of Iceland and Sweden. The match took place in September 2020, in the midst of the second wave of the Covid pandemic which was sweeping through Europe at the time. This visual story illustrates how the Covid pandemic was experienced in a team working quarantine and how it affected the social organisation of the match as shown by established rules and recommendations for human conduct and manifested in new norms of behaviour. The visual story further highlights how the pandemic imposed unprecedented challenges for sport teams to settle the conflicting forces of how to withhold manifested and collective team rituals under such constrains, as for the social organisations, which had to make-up protocols, at short notice, in order to keep the virus at bay. When analysed visually those protocols seemed inconsistent and illogical at times. It can however be argued, that despite those inconsistencies the protocols should be recognised as a responsible act for public welfare as they counter possible public health repercussions associated with such pandemics.